Urgent referral for suspected CNS cancer: which clinical features are associated with a positive predictive value of 3 % or more? - Mohammad, H; Boardman, J; Howell, L; Mills, R; Emsley, H (BioMed Central, 2016)
Background Urgent referral for suspected central nervous system (CNS) cancer is recommended, but little analysis of the referral criteria diagnostic performance has been conducted. New 2015 NICE guidance recommends direct brain imaging for patients with symptoms with positive predictive values (PPV) of 3 %, but further guidance is needed. Methods A 12-month retrospective evaluation of 393 patients referred under previous 2005 NICE 2-week rule criteria was conducted. Analysis was based on the three groups of symptoms forming the referral criteria, (1) CNS symptoms, (2) recent onset headaches, (3) rapidly progressive subacute focal deficit/cognitive/behavioural/personality change. Comparison was made with neuroimaging findings. Results Twelve (3.1 %) of 383 patients who attended clinic had CNS cancer suggesting the combination of clinical judgement and application of 2005 criteria matched the 2015 guideline’s PPV threshold. PPVs for the three groups of symptoms were (1) 4.1 % (95 % CIs 2.0 to 7.4 %), (2) 1.2 % (0.1 to 4.3 %) and (3) 3.7 % (0.1 to 19.0 %). Sensitivities were (1) 83.3 % (95 % CIs 51.6 to 97.9 %), (2) 16.7 % (2.1 to 48.4 %), and (3) 8.3 % (0.2 to 38.5 %); specificities were (1) 37.2 % (32.3 to 42.3 %), (2) 55.5 % (50.3 to 60.7 %) and (3) 93.0 % (89.9 to 95.4 %). Of 288 patients who underwent neuroimaging, 59 (20.5 %) had incidental findings, most commonly cerebrovascular disease. Conclusions The 2015 guidance is less prescriptive than previous criteria making clinical judgement more important. CNS symptoms had greatest sensitivity, while PPVs for CNS symptoms and rapidly progressive subacute deficit/cognitive/behavioural/personality change were closest to 3 %. Recent onset headaches had the lowest sensitivity and PPV.